Improving Students’ Higher Order Thinking Skills Through a Question and Answer Method - Perdy Karuru; Muta’allim; Suparjo; Aan Fatwa Setiawan; Siti Junaida (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2023)
This study explores the transformative impact of a dynamic Question and Answer (Q&A) method on students' higher-order thinking skills. In an era where rote memorization dominates traditional classrooms, this research investigates an innovative pedagogical approach designed to foster critical thinking, problem-solving, and analytical abilities among students. The study employs a mixed-methods research design, integrating qualitative and quantitative analyses to measure the effectiveness of the Q&A method. This research dissects the impact of the Q&A method on cognitive development. It delves into the theoretical foundations of higher-order thinking skills and examines how the interactive nature of the Q&A process stimulates intellectual curiosity. By intertwining challenging questions with collaborative problem-solving activities, educators are empowered to foster an environment where students not only learn but also think critically and creatively. The research results indicate that there are four questioning methods, namely narrative questioning, guessing objects answering method, questioning through body movements, and argumentative questioning. Preliminary findings hint at a positive correlation between the implementation of the Q&A method and significant strides in students' critical thinking abilities. This research goes beyond the conventional boundaries of academia, offering a transformative pedagogical approach that equips students with skills crucial for navigating the complexities of the modern world. By cultivating higher-order thinking skills, this study strives to empower students not only as knowledgeable individuals but as adaptable and innovative thinkers prepared to meet the challenges of the future head-on.